Proust shares the Goncourt brothers’ approach - Campos, Regina Salgado; Silva, Guilherme Ignácio da (Lettres Françaises, 2014)
From the readings of the latest criticism about the importance of the work of Goncourt brothers, the first aim of this study is to establish the relationship of this work with that of Marcel Proust, and second, to present a new commented translation of the pastiche of the Journal des Goncourt, which is in the last volume of Search of Lost Time.